The Influence of Promotional Content on Sales Target Effectiveness in Asik Creative - Nasywaa, Ivena Adinda; Suwaidi, Rahman Amrullah (East Asian Journal of Multidisciplinary Research, 2024)
This research, titled "The Influence of Promotional Content on Sales Target Effectiveness in Asik Creative" employs a quantitative approach to explore the intricate interplay between promotional content and its influence on sales target effectiveness. The study aims to shed light on nuanced aspects, examining how various promotional efforts impact the effectiveness of sales targets. Employing the t-test analysis, the findings yield compelling evidence, establishing a significant correlation between the variables X and Y. This newfound understanding contributes not only to the field of marketing but also provides practical insights for businesses aiming to enhance their sales strategies. The results highlight the pivotal role that targeted promotional content plays in achieving sales objectives and offer valuable implications for optimizing promotional campaigns.